The Influence of Household Composition on Household Expenditure Patterns: Theory and Spanish Evidence - Deaton, Angus S.; Ruiz-Castillo, Javier; Thomas, Duncan (Journal of Political Economy, 1989)
A concept of demographic separability is proposed that formalizes the notion that there are groups of goods (adult goods) that have little or no relationship to specific classes of household demographics (the numbers or ages of children).That there exist adult goods demographically separable from children is a necessary but not sufficient condition for the validity of Rothbarth's method for measuring child costs. We propose two different methods for testing demographic separability and present results from a 1981 survey of Spain. The econometric evidence is in fair agreement with the theoretical presuppositions.